Governance of Family Waqf Companies Between Theory and Practice - DJAFAR HENNI, Mohamed (Journal of Finance & Corporate Governance, 2019)
The effective governance of family waqf companies is a set of rules and regulations that provide accounting information to the board of directors in waqf companies such as disclosure, transparency and clarity, in order to achieve the objectives that benefit the beneficiaries of the services of waqf companies and the dependents and depend on the legal and regulatory systems, Honesty and honesty. The aim of this study is to attempt to construct and formulate the general framework of the governance structure of family waqf companies. This study aims at clarifying the importance of establishing and strengthening the principles of corporate governance in waqf companies. The study found that an effective corporate governance system helps to provide effective and effective trust and transparency to charitable and endowment work. It aims at improving the performance efficiency of Waqf companies and developing their services. Waqf corporate governance also contributes to increasing the mobilization of endowment resources.